Ultrasonic Sensor for Measurement of Water Flow Rate in Horizontal Pipes Using Segment Area - Suryana, Anang; Yudono, Muchtar Ali Setyo (Universitas Nusa Putra, 2023)
Measurement of flow rate in wastewater pipes is still challenging to be done in real-time. The main challenge in wastewater measurement is the non-homogeneity of wastewater due to the presence of solid waste material. This becomes a hindrance when using mechanical flow measurement or direct contact between the fluid and the measuring device. Therefore, the solution is to perform non-contact flow measurement between the fluid and the measuring device. In this study, a flow sensor was developed for a horizontal pipe using the cross-sectional area measurement method on a horizontal pipe measured by an ultrasonic sensor as the fluid level measuring device. The ultrasonic sensor can measure the height of the fluid level, allowing the flow velocity and cross-sectional area of the horizontal pipe to be determined. The basis of this measurement is that any flowing fluid in a pipe that experiences a change in velocity will also experience a change in volume or fluid level. This measurement is in accordance with the continuity equation. From the calibration results, an error of 1.7% was obtained for the height measurement from the ultrasonic sensor compared to the ruler used as a height calibration tool. Meanwhile, the error in the flow velocity measurement from the ultrasonic sensor compared to the calibration results using the tracker software was 4.2%. The error in volume measurement from the ultrasonic sensor compared to the standard measuring tool, a 5-liter beaker glass, was 0.8%. As a conclusion, flow rate measurement using the ultrasonic sensor with the cross-sectional area measurement method can be used to measure the flow rate in a horizontal pipe with a diameter of 11 cm.